EFFECT OF FERTILIZERS, BIOCHAR AND HUMIC ACID ON SEED YIELD AND NUTRIENT CONTENT OF MAIZE (Zea mays L.) GROWN ON ALFISOLS OF TELANGANA - S. A. HUSSAIN, P. MADHAVI, V. SAILAJA, T. RAM PRAKASH and (The Journal of Research, PJTSAU, 2017)
Among cereals, maize (Zea mays L.) is an important food and feed crop which ranks third after wheat and rice in the world. It is a multipurpose cropthat provides food for humans, feed for animals (especially poultry and livestock) and raw material for the industries. This crop has much higher grainprotein content than our staple food rice. Maize is a heavy feeder of nutrients hence it is a very efficient converter of solar energy into dry matter. India is the fifth largest producer of maize in the world contributing 3 per cent of the global production (Arif et al., 2012).